Locality, Equality, and Piety: Pesantren Ecofeminism Movement in Indonesia - Sulistyati, Mardian (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2023)
The ecofeminism movement in Indonesia is generally territorial and intersectional but tends to be secular. This study shows the emergence of ecofeminism ideas integrated with Islamic values in the form of pesantren. Unlike other ecofeminisms—which were generally born as a response to women and environmental issues an sich, pesantren ecofeminism was an effort to rise from the mental-class and economic-class trauma of peasant society. I used a subsistence perspective, which led me to the Pesantren Ekologi Ath-Thaariq in Garut, West Java, Indonesia. I combined Harvard and Longwe frameworks to analyze pesantren’s activity, access, control, and equivalence level. This article contains the pesantren ecofeminism concept in viewing the environment through faith, local wisdom, and piety. This study further examines the ability of pesantren to break unequal power relations between humans and between humans and non-humans, instead of continuing the patriarchal tradition and its kiai-centric system.